Targeted Therapies Combined With Immune Checkpoint Therapy. Issue 2 (March 2016) - Prieto, Peter A.; Reuben, Alexandre; Cooper, Zachary A.; Wargo, Jennifer A.
Abstract : Abstract: The age of personalized medicine continues to evolve within clinical oncology with the arsenal available to clinicians in a variety of malignancies expanding at an exponential rate. The development and advancement of molecular treatment modalities, including targeted therapy and immune checkpoint blockade, continue to flourish. Treatment with targeted therapy (BRAF, MEK, and other small molecule inhibitors) can be associated with swift disease control and high response rates, but limited durability when used as monotherapy. Conversely, treatment with immune checkpoint blockade monotherapy regimens (anti–cytotoxic T-lymphocyte antigen 4 and anti–programmed cell death protein 1/programmed cell death protein 1 ligand) tends to have lower response rates than that observed with BRAF-targeted therapy, although these treatments may offer long-term durable disease control. With the advent of these forms of therapy, there was interest early on in empirically combining targeted therapy with immune checkpoint blockade with the hopes of preserving high response rates and adding durability; however, there is now strong scientific rationale for combining these forms of therapy—and early evidence of synergy in preclinical models of melanoma. Clinical trials combining these strategies are ongoing, and mature data regarding response rates and durability are not yet available. Synergy may ultimately be apparent; however, it has also become clear that complexities exist regarding toxicity when combining these therapies. Nonetheless, this increased appreciation of the complex interplay between oncogenic mutations and antitumor immunity has opened up tremendous opportunities for studying targeted agents and immunotherapy in combination, which extends far beyond melanoma to other solid tumors and also to hematologic malignancies.